Enterprise, Business-Process and Information Systems Modeling 24th International Conference, BPMDS 2023, and 28th International Conference, EMMSAD 2023, Zaragoza, Spain, June 12-13, 2023, Proceedings - van der Aa, Han.; Bork, Dominik; Proper, Henderik A.; Schmidt, Rainer (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book contains the refereed proceedings of two long-running events held along with the CAiSE conference relating to the areas of enterprise, business-process and information systems modeling: * the 24th International Conference on Business Process Modeling, Development and Support, BPMDS 2023, and * the 28th International Conference on Exploring Modeling Methods for Systems Analysis and Development, EMMSAD 2023. The conferences were taking place in Zaragoza, Spain, during June 12-13, 2023. For BPMDS 9 full papers and 2 short papers were carefully reviewed and selected for publication from a total of 26 submissions; for EMMSAD 9 full papers and 3 short papers were accepted from 26 submissions after thorough reviews. The BPMDS papers deal with a broad range of theoretical and applications-based research in business process modeling, development and support. EMMSAD focusses on modeling methods for systems analysis and development.
BPMDS 2023 -- Just Tell Me: Prompt Engineering in Business Process Management -- Reinforcement Learning-supported AB Testing of Business Process Improvements: An Industry Perspective -- Modelling and Execution of Data-Driven Processes with JSON-Nets -- Aligning object-centric event logs with data-centric conceptual models -- From Network Traffic Data to a business-level Event Log -- A Novel Decision Mining Method Considering Multiple Model Paths -- Modeling, Executing and Monitoring IoT-Driven Business Rules -- A Generic Approach towards Location-aware Business Process Execution -- Time-aware Contract Model for Legal Smart Contracts -- Efficient Computation of Behavioral Changes in Declarative Process Models Nicolai Schützenmeier -- Beyond Temporal Dependency: An Ontology-Based Approach to Modeling Causal Structures in Business Processes -- EMMSAD 2023 -- Principles of universal conceptual modeling -- Supporting Method Creation, Adaptation and Execution with a Low-code Approach -- IAT/ML: A Domain-Specific Approach for Discourse Analysis and Processing -- A First Validation of the Enterprise Architecture Debts Concept -- Modeling heterogeneous IT infrastructures: a collaborative component-oriented approach -- Exploring Capability Mapping as a Tool for Digital Transformation: insights from a Case Study -- TEC-MAP: a Taxonomy of Evaluation Criteria for Multi-Modeling Approaches -- Integrating Physical, Digital, and Virtual Modeling Environments in a Collaborative Design Thinking Tool -- Opportunities in Robotic Process Automation by and for Model-Driven Software Engineering -- A Requirements-Driven Framework for Automatic Data Visualization -- Comparing different visualizations for feedback on test execution in a Model-Driven Engineering environment -- Unblocking Inductive Miner - While Preserving Desirable Properties.
Keywords: Information technology -- Management; Business information services; Software engineering; Application software; Computer Application in Administrative Data Processing; IT in Business; Software Engineering; Computer and Information Systems Applications